PELATIHAN KADER KESEHATAN TENTANG PIJAT BAYI DENGAN TEKHNIK TIBBUN NABAWI - Rita Riyanti Kusumadewi; Luluk Fajria Maulida (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Stimulation that can be given to babies is baby massage. Baby massage as a form of touch language has a positive effect on the growth and development of babies. If this touch stimulation is done regularly it can improve blood circulation and increase the catecholamine hormones (epinephrine and neropinephrine) which will trigger growth and growth stimulation which has benefits for increasing appetite, increasing body weight and stimulating the development of brain structure and function. Health cadres are people who are able to be appointed as movers for the community in the field of health, besides that cadres also become a long arm for health workers in embracing the community to achieve better health status. The outputs produced through this program are: articles on infant massage to health cadres. Implementation methods Improve cadre skills on infant massage procedures that can improve baby's health by providing counseling on baby massage, followed by demonstrations and assistance to cadres how to do baby massage with tibbun nabawi techniques. Results in this activity are the majority of health cadres who follow increased skills. Conclusion there has been an increase in the skills of health cadres mothers on how to massage infants with tibbun nabawi techniques.